ROLE OF TARGETED THERAPY IN THE COMBINATION TREATMENT OF PATIENTS WITH KIDNEY CANCER AND METASTATIC BRAIN INVOLVEMENT - D. R. Naskhletashvili; V. A. Gorbunova; A. Kh. Bekyashev; V. B. Karakhan; E. A. Moskvina; E. V. Prozorenko (Опухоли головы и шеи)
In patients with kidney cancer (KC), the rate of metastatic brain involvement is 2-11%, is steadily growing, and is one of the important reasons for treatment failures in these patients. Surgery and radiotherapy, including radiosurgery, must be considered as optimal treatments for patients with KC and brain metastases. Systemic drug therapy has recently played a more and more increasing role in the treatment of patients with a progressive brain tumor process. At the same time, there are no exact pharmacokinetic data on drugs registered for the treatment of disseminated KC in respect to their concentration in the human central nervous when they are used in therapeutic doses. On the basis of the data of the literature review and the results of the authors’ studies, it may be concluded that while none of the target agents has still shown any significant advantage over others in treating KC patients with brain metastases. All the drugs have demonstrated their ability to achieve a clinical and X-ray verified objective effect (as stabilizations in most cases) in treating brain metastases. The most data are available on the therapeutic efficacy of sunitinib and sorafenib. In case of progressive brain tumor process, drug treatment should be individually discussed in each situation in accordance with standard approaches to treating patients with disseminated KC.